DEVELOPING THEMATIC ENGLISH MULTIMEDIA FOR TEACHING VOCABULARY TO YOUNG LEARNERS - Ratnawati, Ratnawati (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2014)
The observed inappropriateness comes from textbooks used in teaching young learners are too difficult, dominated by written form, unspecific, and decontextualized interactive multimedia. Hence, the researcher would like to develop Thematic English Multimedia (TEM) for teaching vocabulary to young learnersat kindergarten B of Islamic Centre Purwodadi, Grobogan. This study employed R&D Design proposed by Borg and Gall (2003:772). Seven stages employed were information and research collecting, planning, developing, validating, revising, try out, and producing final TEM. Observation, interview, validation, performance-based assessment, and pre also post-test were administered to collect data. From results of collected data, they were found that applying TEM got positive perspectives toward teaching and learning process. In line with above statements, TEM is effective and feasible to teach young learners at kindergarten B of Islamic Centre Purwodadi, Grobogan.